The effectiveness of guided reading in the achievement of biology and Quranic comprehension for secondary school students (Journal of the College of Basic Education, 2023)
The aim of the research is to find out the effectiveness of the guided reading method in (achievement and reading comprehension) for the second intermediate students in the subject of biology.To achieve this goal, (68) female students from the second year average were selected in the middle school of progress in the city of Baghdad. The sample members were divided into two groups. The first experimental group studied according to directed reading, while the second group is the control group, which studied according to the usual method. The researcher prepared two tests, an achievement test. And a reading comprehension test for the two groups, and after collecting and correcting the answers, they were processed with appropriate statistical methods. The following is a summary of the research results:The experimental group, which was taught according to guided reading, was superior to the control group in both achievement and reading comprehension.